3‐D thermal analysis for the valve‐side bushings of HVDC converter transformer and application in the evaluation of current‐carrying connections defects. Issue 17 (2nd July 2022) - Lin, Mu; Liu, Kai; Wu, Zihao; Tang, Hao; Liu, Tong; Zhu, Minghui; Wu, Guangning
Abstract: To analyze the overheating problem of the valve‐side bushings of high voltage direct current (HVDC) converter transformer, which is mainly caused by current‐carrying connections defects at copper–aluminium transition region in the bushing, this paper set up a 3‐D electromagnetic‐thermal analysis model for the valve‐side bushings, and a method was proposed to calculate the thermal distribution of the valve‐side bushings under the influence of current‐carrying connections defects. Based on this model, the details of an example were shown in this paper, and the numerical results agreed with the measured results within 1%. Then, the temperature field distribution characteristics of valve‐side bushing under different working current I, defect degree k, and ambient temperature T amb were determined. According to the characteristics, the temperature difference ΔT and working current I of the bushing were applied to evaluate contact resistance at the copper–aluminium transition region of the bushing, which can be provided by a novel method to evaluate for current‐carrying connections defects in the valve‐side bushings.